Effectiveness of Cognitive Behavioral Couple Therapy in Pakistani Couples with Marital Dissatisfaction - Samia Farrukh, Zainab F. Zadeh, Zainab Hussain Bhutto (Pakistan Journal of Psychology, 2014)
This study was designed to evaluate the effectiveness of cognitive behavioral interventions with married couples experiencing marital dissatisfaction. The research design of the study was experimental. Fifty (50) married couples were randomly allocated into two equal groups: the experimental group (the couples received the treatment) and the control group (waited for behavioral interventions).Demographic information was obtained from participants in experimental and control groups. Both groups were assessed for marital adjustment by completing the Dyadic Adjustment Scale (DAS) and the Kansas Marital Satisfaction Scale (KMSS) before (pre-intervention) and after (post-intervention) the cognitive behavioral interventions. The cognitive marital techniques used in the study were adapted from Dattilio (1989). The data was analyzed by using MANOVA and t-tests for post-hoc comparisons. Findings of the study indicated that couples who received cognitive behavioral interventions showed significant reduction in marital dissatisfaction. Study findings have more important implication for the clinicians who are dealing with marital issues.